The social protection indicator for Asia assessing progress. (Asian Development Bank, 2019)
It shows progress in expenditure, primarily driven by social insurance and coverage between 2009 and 2015. Spending on women has improved in several countries, yet others continued to favor the nonpoor over the poor, and men over women. The Social Protection Index now the Social Protection Indicator was developed by the Asian Development Bank and its partners as the first comprehensive and quantitative measure of social protection systems in Asia and the Pacific.